Establishing the cut off values of androgen markers in the assessment of polycystic ovarian syndrome - Nadaraja, R.N. Dineshinee; Sthaneshwar, Pavai; Razali, Nuguelis (College of Pathologists, Academy of Medicine Malaysia, 2018)
Introduction: Hyperandrogenism remains as one of the key features in Polycystic Ovarian Syndrome (PCOS) and can be assessed clinically or determined by biochemical assays. Hirsutism is the most common clinical manifestation of hyperandrogenism. The clinical assessment is subjected to wide variability due to poor interobserver agreement and multiple population factors such as ethnic variation, cosmetic procedures and genetic trait. The difficulty in resolving the androgen excess biochemically is due to a lack of consensus as to which serum androgen should be measured for the diagnosis of PCOS. The aim of the study was to compare and establish the diagnostic cut off value for different androgen biomarker for the diagnosis of PCOS. Materials and Methods: A total of 312 patients classified to PCOS (n = 164) and non PCOS (n = 148) cohorts were selected from the Laboratory Information System (LIS) based on serum total testosterone (TT) and sex hormone binding globulin (SHBG) from the period of 1st April 2015 to 31st March 2016. PCOS was diagnosed based on Rotterdam criteria. Clinical hyperandrogenism and ultrasound polycystic ovarian morphology were obtained from the clinical records. The other relevant biochemical results such as serum luteinizing hormone (LH), follicle stimulating hormone (FSH) and albumin were also obtained from LIS. Free androgen index (FAI), calculated free testosterone (cFT) and calculated bioavailable testosterone (cBT) were calculated for these patients. Receiver Operating Characteristic (ROC) curve analysis were performed for serum TT, SHBG, FAI, cFT, cBT and LH: FSH ratio to determine the best marker to diagnose PCOS. Results: All the androgen parameters (except SHBG) were significantly higher in PCOS patients than in control (p<0.0001). The highest area under curve (AUC) curve was found for cBT followed by cFT and FAI. TT and LH: FSH ratio recorded a lower AUC and the lowest AUC was seen for SHBG. cBT at a cut off value of 0.86 nmol/L had the highest specificity, 83% and positive likelihood ratio (LR) at 3.79. This is followed by FAI at a cut off value of 7.1% with specificity at 82% and cFT at a cut off value of 0.8 pmol/L with specificity at 80%. All three calculated androgen indices (FAI, cFT and cBT) showed good correlation with each other. Furthermore, cFT, FAI and calculated BT were shown to be more specific with higher positive likelihood ratio than measured androgen markers. Conclusions: Based on our study, the calculated testosterone indices such as FAI, cBT and cFT are useful markers to distinguish PCOS from non-PCOS. Owing to ease of calculation, FAI can be incorporated in LIS and can be reported with TT and SHBG. This will be helpful for clinician to diagnose hyperandrogenism in PCOS.